Differences Between Amblyopic and Fellow Eyes in Optical Coherence Tomography: A Cohort from Jordanian Population - Noor M. Alqudah; Hasan Mohidat; Abdelwahab Aleshawi; Wedad Al-Dolat; Ali Alshami (Medicina)
Background and Objectives: Amblyopia is a condition where children undergo unilateral or bilateral vision loss due to a variety of disorders that impact the visual pathway. The assessment of retinal nerve fiber layer (RNFL) thickness in amblyopia has made optical coherence tomography (OCT) a useful technique for studying the pathophysiology of this condition. This study was conducted to assess OCT results for various forms of amblyopia, including macular thickness and peripapillary RNFL thickness. It is the first of its kind in Jordan. Materials and Methods: Sixty-one individuals, aged 14 to 67, who had been diagnosed with unilateral amblyopia participated in a prospective study. Both eyes underwent spectral-domain OCT imaging, and clinical and demographic information was gathered. Relationships between different types of amblyopia and OCT measurements were investigated. Results: Compared to the contralateral fellow eyes, the amblyopic eyes showed thicker fovea, and there were differences in foveal and macular thickness observed between the sexes. Individuals with anisometropic amblyopia exhibited a greater central macular thickness. While nasal optic nerve thickness was adversely correlated with age, inferior optic nerve thickness was considerably lower in amblyopia. Conclusions: This research indicates unique OCT traits in amblyopic eyes, which may have a role in amblyopia diagnosis and treatment. The prevention of long-term visual impairment depends heavily on early detection and care. More studies using larger cohorts and longitudinal designs are necessary to improve our knowledge of the pathogenesis of amblyopia and to provide the best possible clinical management approaches.